Kearifan Lokal Dalam Peningkatan Kesadaran Hukum - Muhammad Ruhly Kesuma Dinata; Syafruddin Syafruddin (Rechtsregel : Jurnal Ilmu Hukum, 2021)
Law which is seen as one of the important aspects in society that aims to realize the formation of a comfortable and just society, is sometimes ignored by a few people. Not infrequently the law is injured, violated, even manipulated its function by people who do have an interest or people who still consider the importance of a law that exists in society. North Lampung as one of the districts in Lampung Province which has an area of 2,765.63 km² and the total population of the district is 612,100. In 2020 in September at the Resort Police (Porles) of North Lampung, reports of the occurrence of crime have exceeded 1000 (one thousand) reports, this is very concerned about legal awareness in North Lampung. Whereas in the North Lampung community, it is very thick with Lampung Indigenous culture which has behavioral values in the community called Piil Pesinggiri which is defined as a sense of shame to carry out an attitude that is insulted by religion and socio-cultural environment.